Interventions for Perinatal Depression and Anxiety in Fathers: A Mini-Review - Rodrigues, Andre L.; Ericksen, Jennifer; Watson, Brittany; Gemmill, Alan W.; Milgrom, Jeannette (Frontiers in Psychology, 2022)
Background and Objectives Up to 10% of fathers experience perinatal depression, often accompanied by anxiety, with a detrimental impact on the emotional and behavioural development of infants. Yet, few evidence-based interventions specifically for paternal perinatal depression or anxiety exist, and few depressed or anxious fathers engage with support. This mini-review aims to build on the evidence base set by other recent systematic reviews by synthesising more recently available studies on interventions for paternal perinatal depression and anxiety. Secondarily, we also aimed to identify useful information on key implementation strategies, if any, that increase the engagement of men. Methods We drew upon three major previous systematic reviews and performed an updated search of PubMed/Medline; Psycinfo; Cochrane Database; Embase and Cinahl. The search was limited to trials, feasibility studies or pilot studies of interventions published between 2015 and 2020 that reported on fathers' perinatal mental health. We included psychological, educational, psychosocial, paternal, couple-focused, or group therapies, delivered face-to-face, via telephone and/or online that reported on either paternal depression, anxiety or both. Results Eleven studies satisfied search criteria (5 of which were not included in previous reviews). The majority were randomised controlled trials. Most interventions incorporated counselling, therapy or psychoeducation and took an indirect approach to perinatal mental health through antenatal or postnatal education and were couple-focused. No studies reported a presence of diagnosed depression or anxiety at baseline, although five studies reported a positive effect on sub-threshold symptoms. Discussion There was some evidence that these approaches may be useful in the initial engagement of fathers with perinatal supports and improve depression and anxiety scores. No studies targeted the explicit treatment of clinically depressed or anxious men, and this remains the most substantial gap in the peer-reviewed evidence base. Our results highlight the need to deliver perinatal interventions specifically designed for men and evaluate them in populations with clinical levels of depressive and anxious symptomatology.